Food Processing Learning Strategies for Vocational High School Students Majoring in Culinary Arts in Tondano, Minahasa Regency: Opportunities and Challenges - Louisa Kandoli (Jurnal Pendidikan Non formal, 2025)
This study aims to analyze learning strategies for processing food applied to students of Vocational High School (SMK) majoring in culinary arts in Tondano, Minahasa Regency, and to examine the opportunities and challenges faced in the implementation process. Research: This use-method study literature with a qualitative approach combined with contextual analysis. Search article in the Scopus database, with publications from 2020–2026, using the keywords "food", "process", and "vocational" to obtain relevant literature on learning to process food in vocational education. Selected articles were then analyzed using a bibliographic use tool, Soft VOSviewer, through network visualization to map interword relatedness, identify key themes, and see the trend of topic research. Research results show that learning about food in vocational education is closely related to learning strategies, student and teacher roles, industry relevance, and learning evaluation results. Visualization network confirms that learning is not only process-oriented but also results-oriented, in the form of a product that is applicable and useful. Findings. This emphasizes the importance of learning contextual, practice-based skills for vocational school students majoring in culinary arts. If associated with the context of Tondano, Minahasa Regency, there is a big opportunity to develop learning based on local potential, such as traditional food materials, local agricultural practices and animal husbandry, as well as Minahasa culinary culture. However, the challenge still faced, including limitations, means practice, lack of innovation, a gap between the curriculum and industry needs, as well as the influence of modern culinary trends. Therefore, adaptive, collaborative, and learner-based learning strategies are needed. wisdom local to be sustainable.